Board Monitoring, Consulting, and Reward Structures* - DRYMIOTES, GEORGE; SIVARAMAKRISHNAN, KONDURU (Contemporary Accounting Research, 2012)
Recent work in the corporate governance literature stresses the need to provide boards of directors (BoDs) with explicit incentives to safeguard shareholder welfare (Bebchuk, Fried, and Walker 2002; Bebchuk and Fried 2004). Jensen (1993) observes that “encouraging outside board members to hold substantial equity interests would provide better incentives.” In a similar spirit, the National Association of Corporate Directors (National Association of Corporate Directors 1995) proposed that “boards should pay directors solely in the form of stock and cash — with equity representing a substantial portion of the total up to 100 percent.” Indeed, equity-based BoD compensation has been on the rise in recent years (Bhagat and Black 2002; Conference Board 2006; Pearl Meyer & Partners 2007).1 The underlying premise is that equity awards help align BoD incentives with shareholder interests and enhance long-term firm value (Byrne 1996; Gabrielle 2001). However, to the extent that directors hold both vested and unvested (restricted) equity-based instruments, their actions are likely influenced by a combination of short-term and long-term incentives. The literature has focused mainly on the beneficial long-term incentive effects of equity awards. However, the effects of accompanying short-term incentives are not clear. Are they non–value adding, or do they in fact affect BoD behavior in a way that benefits shareholders? We address these questions in this paper. In particular, our purpose is to jointly examine the short-term and long-term incentive effects of equity-based BoD compensation on the BoD’s corporate governance (contracting and monitoring) and advisory (consulting) roles.2 The boards’ corporate governance role has been examined extensively.3 However, directors are typically individuals with considerable management experience and expertise and serve as a natural resource for top management in making crucial strategic and operational decisions.4,5 In fact, surveys have indicated that most directors view advising as their primary role (Mace 1972; Demb and Neubauer 1992; Adams 2009). Nevertheless, the BoD’s advisory role has received relatively little attention in the literature. Adams and Ferreira (2007), for example, examine the BoD’s monitoring and advisory role and show that a less independent BoD is sometimes optimal because it is less likely to monitor management, which, in turn, induces management to share information with the BoD, and receive better advice leading to greater investment efficiency.6 If this advisory role is indeed value-enhancing for shareholders, it cannot be ignored when examining the short-term and long-term incentive effects of BoD compensation. We use a simple agency model in which the BoD performs three roles: contracting, monitoring and consulting. The BoD contracts with the manager to supply some productive input that results in firm output. A performance evaluation system that produces an informative signal about firm output, and consequently about managerial effort, is used to contract with the manager. By monitoring, the BoD improves the precision of this information signal. By serving as a consultant, the BoD makes the manager more productive, that in turn means higher expected firm output. The BoD and the manager’s inputs are unobservable and personally costly.7 We assume that board members are themselves rational and self-serving, and must be motivated to provide consulting and monitoring inputs. Consequently, there are two agency problems in our model. The first is between the BoD and the manager, and the second is between the BoD and the shareholders. Both the agency problems arise because the BoD and manager’s respective inputs are unobservable and personally costly. In this respect, our paper adds to the growing literature that models shareholder-manager conflict as arising from a two-tier agency relationship. In our context, a single-tier model that examines shareholder-manager agency conflict stemming from the separation of ownership and control does not permit a role for the BoD. Therefore, by examining a multi-tier agency relationship our paper helps us better understand organizations (Bolton and Scharfstein 1998). In related work, Kumar and Sivaramakrishnan (2008) examine the BoD’s corporate governance role using a double agency model. They focus on the impact of the lack of BoD independence from management on corporate governance, and characterize optimal equity awards to the BoD to create the right BoD incentives. Harris and Raviv (2008) present a model where control of the board can be given to either insiders (the non-independent board) or outsiders (the independent board) — both insiders and outsiders have private payoff-related information. They show that it is sometimes beneficial to give board control to insiders in order to better exploit their information. We begin our analysis by examining a benchmark setting in which the BoD’s inputs are commonly observable. In this benchmark case, it suffices to compensate the BoD for the personal cost of providing consulting and monitoring inputs. When the BoD’s inputs are not observable, explicit BoD incentives become necessary. We show that long-term incentives (i.e., incentives tied to firm output) make the BoD explicitly care about the firm’s output and thereby motivate the BoD to play an active consulting role. Thus, compensating the BoD with restricted stock awards (equity) motivates the BoD to supply consulting input. However, we identify conditions under which long-term incentives alone do not suffice in motivating the BoD’s monitoring input. The is that the BoD’s monitoring input improves the of the performance evaluation system used to managerial and has on firm output. The BoD, does not have incentive to supply monitoring input. the need for short-term incentives. We show that incentives tied to the short-term used to are in this because they provide incentives for the BoD to in We are not of work that has the role of short-term BoD incentives in this short-term BoD a that the manager can these in for private the BoD or We address this by a setting where the manager can the firm’s short-term and show in the use of short-term induces the BoD to monitoring In our results that both long-term and short-term incentives are to that the BoD both corporate governance and consulting equity awards are in the with to equity awards are in motivating In we are to of BoD compensation to BoD The paper as In we the model. In we the BoD’s consulting and monitoring inputs. In we the effects of providing short-term long-term incentives to the BoD. In we the where the manager can firm We provide a and some in where is the of is the manager’s is the manager’s productive effort, and is the cost of productive to the manager. The manager’s productive input is unobservable to the BoD. we assume it is where actions that are in the interests of the shareholders. of we assume that productive is personally to the The output of the by is a from the with The BoD has the expertise to as a to the manager. from simple advice to the manager to providing on and the firm’s and We assume that the manager’s Thus, the BoD’s expertise and the manager a We do not on the of and for the that the BoD’s consulting input can have a more impact on the manager’s when the manager either or productive We assume that the firm’s expected output on productive effort, of the BoD’s consulting is that the productive that We assume that the firm’s output, is not the short-term of the manager. Therefore, the manager cannot be a that a of this output. the manager to be on an and short-term which we by by a performance system in performance can of two where We can of as a short-term of the output. we assume that the manager does not have the to this we this The that the manager cannot be a contract on the long-term output some the manager’s contract can be on long-term the optimal compensation contract would be a of is a of there is that in short-term performance play a role in managerial is literature on managerial or that can be to the to short-term and Bebchuk and (1993) show that focus on short-term performance in model this by the manager’s that a contract on short-term performance is of our model is that the BoD’s consulting and monitoring inputs are unobservable to the manager, as is the manager’s to the BoD. Both the BoD and the manager must be motivated to supply their respective inputs. in the the BoD is with restricted and We assume that restricted equity awards have a that the firm’s output or value observable. Thus, the value of restricted equity awards on the of of compensation we use the restricted equity awards to to BoD compensation on the firm’s output of compensation for of the the value of equity awards on the firm’s short-term which is by awards be as a short-term incentive when there are on as a we use the equity awards to to BoD compensation on The manager’s compensation is on short-term performance — the of the performance the contract to the by the BoD. The BoD’s on the can be on both short-term and long-term and We use to the contract to the BoD by the shareholders. We are in that directors have an that has example, that directors their a of the of the fact that the is for both and that a of their between the of and outside in their is to the Board the of directors on boards is years of directors have for more the is The of is as the BoD a compensation contract to the manager. If the manager the or productive the BoD monitoring and consulting inputs. performance is and are as of that by monitoring input the BoD makes the short-term performance a less signal about the firm’s output Consequently, by monitoring the BoD improves the of about the manager’s productive input and can the manager productive a expected compensation The BoD’s consulting on the the manager’s and firm output, it can for the BoD’s monitoring role. The BoD’s consulting input the of the short-term performance a on it the of consulting can or the of about the manager’s productive on consulting input is more informative on consulting input the is a of the in the can a or a in the manager. an where the BoD’s consulting the manager’s it the that on productive by the manager, making about the manager’s makes it more likely that the manager is for Thus, consulting in this the role of and thereby results in expected compensation the where means that the signal more likely with consulting when the manager productive making about the manager’s more more for the manager. a higher compensation is to the manager to supply productive In the of and which of these two effects and the BoD’s consulting input improves or the of the short-term performance about the manager’s productive input We can the has a on the manager’s performance evaluation by the of the short-term performance about the manager’s productive to consulting and in the of has a on the manager’s performance evaluation by the of the short-term performance about the manager’s productive to consulting and in the of If the of consulting on the of the short-term performance about the manager’s productive to consulting and in the of is is to that we are the of on consulting and consulting input. Thus, consulting the role of monitoring in our model. the consulting has an on the of with to the manager’s productive input. The BoD’s consulting input the manager’s the adds some to the performance evaluation that conditions and are conditions and it is that of In the impact of the BoD’s consulting input on the of and on the manager’s performance is for or effects of BoD consulting makes the model more the that the role the short-term performance and the long-term value play in motivating the BoD the become to We to the effects of the BoD’s consulting and monitoring inputs using the by and in the effects of and in the of and consulting the of about the manager’s productive and the of to which the manager is in Consequently, we can identify a of for which the manager’s by the to the is not us to the effects of consulting and The focus of is on the manager’s expected compensation and on However, in the of or are on the manager’s Therefore, on the us to identify a of that for of monitoring, consulting does not affect the of the of the we focus on the of for which the BoD’s consulting does not affect the of with to the managerial productive input. We begin our analysis by examining a where the BoD’s monitoring and consulting inputs are commonly and the manager productive input (the manager’s productive input is not setting a benchmark which we the benefits from providing short-term and long-term incentives to the BoD when the BoD’s inputs are not observable. In this benchmark explicit incentives are to motivate the BoD to provide these it suffices to compensate the BoD for the of these inputs. Thus, the that the BoD monitoring input the from monitoring — expected compensation cost — the BoD’s cost of the the BoD consulting input they a If consulting has a on the manager’s performance the consulting input from the BoD the from and expected managerial compensation the BoD’s cost of consulting. If on the consulting has a the consulting input from the BoD the from the in expected managerial compensation and the BoD’s cost of consulting. We this in the In the benchmark the the BoD consulting monitoring inputs in the benefits from these inputs the BoD’s cost of monitoring and consulting. We a setting in which these inputs are unobservable to the manager and to outside shareholders. setting us to examine the role of short-term and long-term BoD In BoD compensation vested stock and equity the value of these is by short-term is to examine the role of short-term BoD incentives in motivating their consulting and monitoring we first characterize the BoD’s optimal compensation contract on and on and We examine the optimal contract can the form of a to the BoD on short-term performance and restricted equity stock tied to long-term and the BoD’s and of we to and assume the monitoring and consulting by the BoD. In the benchmark the BoD’s monitoring input the of the short-term performance about the manager’s productive a monitoring the BoD to that in the manager productive a expected compensation However, a BoD contract on long-term performance does not the BoD’s compensation to or the manager’s compensation — monitoring improves the precision of about to is not to compensate the BoD on long-term performance and that it monitoring input in can that the BoD consulting input in The is to the firm’s expected output of the BoD’s and manager’s compensation. The the BoD and the that the BoD consulting input. the that BoD are The to that the BoD monitoring and consulting inputs in using a contract on to the need to compensate the BoD on both short-term and long-term that the BoD’s cost of monitoring input does not affect the BoD’s compensation the cost of monitoring to the cost of consulting is that the firm the BoD consulting input in by the BoD when this the BoD monitoring input. that both monitoring and consulting affect the In this case, that the BoD consulting input does not monitoring input. The BoD has to be explicitly for the cost of monitoring, in to the cost of to supply monitoring and consulting inputs in contract the that are more likely when the BoD monitoring input. monitoring is that the firm must provide incentive for the BoD to supply monitoring input in and which are the two that become more likely when the BoD monitoring input — by monitoring improves the precision of about by the that is when the firm’s long-term performance is that the BoD optimal of the cost of monitoring to the cost of consulting is a of both short-term and long-term Thus, the BoD’s compensation to both short-term and long-term and is to that the BoD consulting and monitoring inputs in We this in the does not a BoD contract on long-term performance that the BoD monitoring input. A BoD contract that is on both long-term and short-term and is to that the BoD consulting and monitoring inputs in The BoD optimal the BoD for of short-term and long-term and we to examine the optimal BoD contract can be a that is on short-term performance and a that is on long-term it the optimal BoD contract can be short-term and long-term We can the which conditions under which the optimal BoD contract can the form of a on the short-term performance and restricted equity stock value is tied to the output The can that the BoD monitoring and consulting input in by the BoD a contract of the form If If We focus on with in which to a of BoD compensation short-term and long-term is to that does not the incentive effects of BoD equity awards. In particular, equity awards and long-term performance incentives as are not because the BoD with equity makes a of the firm’s output — firm output compensation — of Nevertheless, we a more in our analysis and our attention to contracts of the form where a share of the firm given to the BoD, and a a us to to the role of equity awards in the BoD compensation is similar to that in the benchmark for the incentive that the BoD’s monitoring and consulting inputs. equity as in share the BoD to care about the firm’s expected long-term that given a equity the BoD would in the However, as we in restricted equity awards are not in motivating monitoring input. the BoD that the manager has productive effort, it does not by to the of the performance about the manager’s productive has incentive to monitoring that given the the BoD’s consulting input the of about the manager’s productive restricted equity awards provide incentive to the BoD to that the manager productive the as the BoD a portion of that incentive to the BoD to not monitoring If the BoD that the manager has productive effort, it not supply monitoring input to the that and thereby the manager’s expected compensation as is to that the BoD’s incentive to not supply monitoring input does not solely on to the manager’s expected compensation. Therefore, we identify the equity to motivate the consulting the the BoD’s consulting input results in higher expected firm output that the BoD some equity their The must the benefits and with the BoD’s consulting input in and equity to to the BoD. equity is for shareholders, it does not make to have the BoD provide consulting input in The BoD’s incentive to not supply monitoring input some In our it is rational for the BoD to not supply monitoring input there that this example, directors have personal with the manager of the If we to the effects of the BoD’s personal cost of monitoring suffices to that restricted equity awards cannot motivate the BoD to supply monitoring input in The of this is as The is that is of the BoD’s and the We can the The can be by to the that consulting long-term firm value and monitoring has short-term in turn that the BoD’s compensation has to be tied to both short-term and long-term Indeed, that restricted equity awards are to that the BoD consulting and that equity awards are to that the BoD monitoring role. the BoD’s compensation to the long-term performance of the firm — restricted equity awards — is the BoD’s compensation to the firm’s short-term performance does not to be that as we have the BoD, the manager, must be for short-term The If a performance is to it is for setting BoD incentives as The use of short-term performance in setting BoD incentives is with an in that it the BoD to performance by for management — on which there is little — is that is a performance and have the incentive to in a way that on by using their it is the of the to that the and the performance of a firm in a the BoD has a to shareholder Thus, it would that in setting BoD the use of performance that are to managerial incentives does not help this this it is more likely that when the firm’s output is of managerial the analysis we assume that does not a personal cost to the manager does it affect or If it the manager would in or expected from is greater the this cost an it does not affect our analysis is to show that in the manager indeed to productive the BoD has to short-term that is the manager in to or expected BoD monitoring the effects of does not the manager’s incentive to the BoD this behavior by the manager and that or is to or However, results in higher expected compensation because the performance evaluation system is less because it is more for the BoD to the manager’s productive input. The manager the firm’s short-term performance in results in higher expected compensation We examine the BoD’s compensation incentives to monitor the manager in the of performance We first the role of long-term BoD incentives. We that compensating the BoD with an equity share does not give the BoD incentive to supply monitoring input in The is similar to the The is that the BoD’s monitoring input is for the BoD and it improves the of about the manager’s productive the fact that monitoring the of performance by the manager the BoD that the manager productive in the BoD does not by monitoring input. an equity share the BoD not supply monitoring input. the use of the short-term BoD incentives. that on monitoring the of and thereby the of the the of on by the that the BoD that the manager productive in is more likely to means that the the BoD short-term they can that the BoD monitoring input in short-term BoD incentives incentive with to monitoring role in the of performance The of providing corporate boards with long-term incentives equity awards has been by recent corporate governance literature. as a most directors hold both vested and unvested (restricted) equity and their actions are likely influenced by a combination of short-term and long-term incentives. it would that long-term incentives should suffice in that boards to shareholder the effects of short-term incentives are not clear. In this we examine the effects of short-term and long-term incentives on the corporate governance (contracting and monitoring) and management advisory (consulting) of the BoD using a two-tier agency primary is that long-term incentives not suffice and that short-term BoD incentives can play a role in shareholder as restricted equity provide the BoD with the incentive to supply consulting by not motivate the BoD to monitor when monitoring is personally to the BoD. By short-term incentives BoD as or a on short-term can the BoD contracting, and monitoring more short-term serve an incentive role in the of long-term incentives. of our model some we have on a simple to these In particular, the that are be as there is considerable in the agency literature in this If we this and it is that the not the manager to the and not the BoD to the monitoring However, the underlying incentive is the as in our model. in the results of the we the effects of the BoD’s consulting and monitoring inputs on the of the short-term about the manager’s In particular, we conditions that the BoD’s consulting input has or with to the of the short-term when helps the it is not necessary. results and hold when we for of the BoD’s consulting input. We that managerial is a primary BoD Recent corporate governance as the of shareholder and shareholder to directors have this In our monitoring is not a for is because the way can in our model is the manager to supply productive when is expected to supply productive there is in — the manager productive In in our managerial is and monitoring can be as the cost of in where we performance we do not view monitoring as a way to the improves the precision of the performance and the effects of it does not the BoD to If the BoD with some managerial a would that the manager does not in The role of short-term BoD incentives in a setting where the primary is is not clear. be an for is to that shareholder and BoD interests be for can create incentives for directors to provide consulting and monitoring inputs the for directors of is is that directors some benefits personal or have for when be as directors for short-term In this the of boards that directors can serve as and shareholder and not be in the our analysis makes a for providing explicit incentives to align interests and of the BoD, a recent by to a a in the by making corporate boards more and to have been in to recent the of stock by some address this the cost of incentive that we have in this paper. We use and to conditions that the BoD’s consulting input improves or the of about the manager’s productive input. can be that the of to that is and as Thus, We the to We that that Therefore, the of about the manager’s productive input improves when the BoD consulting can be that the of to the as we can that We to identify conditions that the of and for that the BoD’s consulting input does not affect the manager’s expected compensation we the by and to the effects of and we to identify conditions that when the the as an of and the manager’s the is The is to the firm’s expected output of the BoD’s and manager’s compensation. The the BoD and the that the BoD consulting input. the that BoD are The is to the firm’s expected output of the BoD’s and manager’s compensation. The the BoD and the that the BoD monitoring and consulting inputs. the that BoD are that both monitoring and consulting cost affect the optimal The optimal BoD contract that consulting and monitoring inputs in is in the of contract can be a contract of the form The BoD’s monitoring input improves the of the performance about the manager’s productive However, the BoD that the manager productive effort, it has incentive to monitoring equity awards do not the fact that the BoD does not by monitoring effort, personal cost for the BoD that the manager productive effort, it has incentive to monitoring for an The optimal compensation contract that the manager in that and monitoring the of on a the BoD can the manager’s expected compensation by monitoring The manager this behavior by the BoD and does not a contract on monitoring The BoD supply consulting input in The way the BoD can the manager from firm performance is to a compensation the manager productive in A rational BoD this behavior by the manager and the compensation contract to the manager productive and does not that makes productive more for the manager. on and is more likely to the of on and a the BoD higher expected compensation to the manager productive in more to the of in where a similar has been the fact that monitoring the effects of the manager’s the BoD does not have incentive to supply monitoring input it is with an equity share in the The is that monitoring is personally for the BoD and monitoring improves the of the performance about the manager’s productive Thus, the BoD that the manager has productive in it has incentive to supply monitoring We have in that in a setting a combination of short-term and long-term incentives can that the BoD consulting and monitoring inputs in can be to the In the between the and is that the that is when the firm’s output is is in the setting and in the Thus, similar as in the of it can be that a combination of short-term and long-term incentive can that the BoD consulting and monitoring inputs in that the manager’s to firm performance on the compensation